The relationship between emotional intelligence and job performance among secondary school teachers / Nor Farihin Ariffin - Ariffin, Nor Farihin (2019)
The purpose of this study was to determine whether there is a relationship between emotional intelligence and job performance among secondary school teachers. This study examined the relationship between emotional intelligence which consists of four dimensions: self-awareness, self-regulation, social awareness and relationship management with the job performance of the teachers. The respondents of this study were 196 teachers from five secondary schools in Dungun. Data was collected through questionnaire and analysed using the IBM SPSS Version 22 Software. Overall, it is hoped that this study will give benefits and positive impacts to the school administrators as well as to the Malaysian Education System in dealing with teachers’ performance.